Corrosion Investigation of Commercially Available Linepipe Steel in CO2 Environment - Haris, Muhammad; Kakooei, Saeid; Che Ismail, Mokhtar (International Journal of Engineering and Technology, 2018)
CO2 corrosion has been the most prevalent form of corrosion and is considered as a complex problem in oil and gas production industries. The CO2 in presence of water causes sweet corrosion that is responsible for failure of pipeline during transportation of Oil and Gas. This work studies the corrosion behaviour of carbon steel specimens in CO2 environment at different temperatures but at constant pressure. The effect of CO2 on Carbon Steel specimens (X65, A106) were studied in simulated solution of 3 wt.% NaCl. The specimens were immersed into the CO2 containing solution for 48 hours and corrosion behaviour was investigated by using electrochemical test like Linear Polarization Resistance and Tafel plot. The results indicate that the temperature has an important effect of corrosion rate of carbon Steel in CO2 environment. Corrosion rate of 1.5-2 mm/yr was reported for both steels at lower temperature while at higher temperature the difference can be observed due to difference in protective nature of steels. Similar Corrosion rate around 1.5 -2 mm/yr was observed at 25Â°C for both A106 and X65 while at 50Â°C and 75Â°C the corrosion rate varies significantly 1.5-3 mm/yr and 3.5-6 mm/yr.Â Â